Financial Inclusion and Financial Stability: The Case of Islamic Rural Banking in Indonesia - Sururi, Sururi; Agus Kuntoro (Accounting and Finance Studies, 2025)
Research Aims: This study aims to examine the relationship between financial inclusion and financial stability in the context of Islamic rural banks in Indonesia. Additionally, it incorporates bank-specific factors and macroeconomic conditions as independent variables. Design/methodology/approach: This research employs a quantitative approach using the Autoregressive Distributed Lag (ARDL) model, with time series data from January 2014 to June 2024. Research Findings: The findings reveal that financial inclusion does not significantly impact financial stability, which may be due to the limited accessibility of financial services for low-income populations. Furthermore, capital adequacy, profitability, and exchange rates generally have a positive influence on financial stability. On the other hand, credit risk, bank size, and inflation negatively affect financial stability. However, liquidity shows no significant effect on financial stability. Theoretical Contribution/Originality: This study contributes to the limited research on the relationship between financial inclusion and financial stability, specifically within the context of Islamic rural banks. Additionally, it employs a financial inclusion index to measure financial inclusion, adding a unique methodological approach to the existing literature.